Candida/Candida biofilms. First description of dual-species Candida albicans/C. rugosa biofilm - Martins, Carlos Henrique Gomes; Pires, Regina Helena [UNESP]; Cunha, Aline Oliveira; Pereira, Cristiane Aparecida Martins; Singulani, Junya de Lacorte [UNESP]; Abrão, Fariza; Moraes, Thais de; Mendes-Giannini, Maria José Soares [UNESP] (Elsevier, 2016)
Denture liners have physical properties that favour plaque accumulation and colonization by Candida species, irritating oral tissues and causing denture stomatitis. To isolate and determine the incidence of oral Candida species in dental prostheses, oral swabs were collected from the dental prostheses of 66 patients. All the strains were screened for their ability to form biofilms; both monospecies and dual-species combinations were tested. Candida albicans (63 %) was the most frequently isolated microorganism; Candida tropicalis (14 %), Candida glabrata (13 %), Candida rugosa (5 %), Candida parapsilosis (3 %), and Candida krusei (2 %) were also detected. The XTT assay showed that C. albicans SC5314 possessed a biofilm-forming ability significantly higher (p < 0.001) than non-albicans Candida strains, after 6 h 37 °C. The total C. albicans CFU from a dual-species biofilm was less than the total CFU of a monospecies C. albicans biofilm. In contrast to the profuse hyphae verified in monospecies C. albicans biofilms, micrographies showed that the C. albicans/non-albicans Candida biofilms consisted of sparse yeast forms and profuse budding yeast cells that generated a network. These results suggested that C. albicans and the tested Candida species could co-exist in biofilms displaying apparent antagonism. The study provide the first description of C. albicans/C. rugosa mixed biofilm.
Keywords: Candida rugosa; Dual-species biofilms; Fungal biofilms; Oral colonization; Prostheses-related infections